Effects of Tai Chi practice through virtual training on attentional inhibition and response inhibition among students of USM, Kelantan, Malaysia - Chuan, Chang Shu (2022)
Introduction: Tai Chi was shown to be effective in improving cognition as it is a mind-body exercise which incorporates the flow of the movements as well as breathing technique. In the current study, Tai Chi was used to act the intervention in order to study its effect on response inhibition and attentional inhibition among healthy young adults. Method: This is an interventional study with convenience sampling method. The target population was students from School of Dental and Health Sciences in Universiti Sains Malaysia, Kubang Kerian. All participants had fulfilled the subject criteria and passed both the screening tests. There were two screening tests which were the Ishihara Color Blindness Test and Physical Activity Readiness Questionnaire (PAR-Q). The sample size of this study consisted of 31 (F =21, M =10) participants. The intervention was carried out using Yang-styled Tai Chi which is simplified version of Tai Chi. Pre and post assessments included Antisaccade task that measure response inhibition and Visual search task that measure attentional inhibition. Both Antisaccade task and Visual search task were done with the use of eye tracker. To analyse the collected data, both SMI BeGaze and Statistical Package for Social Sciences version 26 were utilized. Results: The statistical test that was used to analyse the collected data was paired sample t-test. In both cognitive tasks, participants’ response time and accuracy were included. For response inhibition, there were significant improvements in accuracy and response time between pre and post assessment. There was a significant difference in the accuracy for pre intervention (M=10.27, SD=8.72) and post intervention (M=.86, SD=1.66); t(30)=-6.17, p < .001. There was a significant difference in the reaction time for pre intervention (M=230.99, SD=265.10) and post intervention (M=157.78, SD=144.75); t(1633)=-10.04, p < .001. For attentional inhibition, there was a significant improvement in response time between pre and post assessment of Visual search task but not n accuracy. There was no significant difference in the accuracy for pre intervention (M= .89, SD=1.46) and post intervention (M=.32, SD=.80); t(30)=-1.83, p = 0.07. There was a significant difference in the reaction time for pre intervention (M= 634.84, SD=465.66) and post intervention (M=462.92, SD=364.48); t(962)=-172.93, p < .01. Conclusions: Tai Chi training used in this study was able to significantly improve cognition, particularly response inhibition in terms of accuracy and reaction time while attentional inhibition in terms of reaction time among USM students.